Irreducibility and Asymptotics of Stochastic Burgers Equation Driven by α-stable Processes - Feng-yu Wang (Potential Analysis, 2018)
The irreducibility, moderate deviation principle and $ψ$-uniformly exponential ergodicity with $ψ(x):=1+\|x\|_0$ are proved for stochastic Burgers equation driven by the $å$-stable processes for $å\in (1,2),$ where the first two are new for the present model, and the last strengthens the exponential ergodicity under total variational norm derived in \cite{Do-Xu-Zh-14}.